Efektivitas dan Efisiensi Pelaksanaan Anggaran Belanja Dalam Menilai Kinerja Keuangan Pada Balai Besar Karantina Pertanian Makassar - Baharuddin Baharuddin (STIM-LPI Makassar, 2021)
The type of research used in this study is descriptive research. The sample identified in the survey conducted by the researcher is the data of the 2018-2020 budget realization report. the financial performance of the Makassar Agricultural Quarantine Center has been effective because the results achieved are 90% and above This can show that the effectiveness of the implementation of the budget budgeted at the Makassar Agricultural Quarantine Center has been effective and well realized by the Makassar Agricultural Quarantine Center itself, for a period of 3 (three) years by increasing the level of its effectiveness. kinerja keuangan pelaksanaan anggaran belanja Balai Besar Karantina Pertanian Makassar sudah mencapai kriteria sangat efisien dalam hal pengelolaan anggarannya. Jadi, pengelolaan anggaran belanja Balai Besar Karantina Pertanian Makassar telah berhasil dan memenuhi syarat/kriteria efisiensi yaitu penggunaan dana minimum untuk mencapai target/sasaran